New geostrategic challenges of tourism in the context of sustainable development - Kovalskyi, Maksym; Blyznyuk , Andrii; Chip , Liudmyla; Pylypenko , Kateryna; Shcheblykina , Inna (Interacción y Perspectiva, 2023)
Geostrategy is a term that combines geographic factors with political elements that must be taken into account to design development plans to rationally exploit the existing resources in a community. One of the most lucrative and profitable economic activities is tourism, which justifies exploring the potential of this activity from the field of geostrategy. The objective of this article is to identify the new geostrategic challenges of tourism in the context of sustainable development, with a social perspective. In order to achieve the proposed objective, a hermeneutic methodology was used with a predominance of digital documentary sources, whose main theme was the relationship between geostrategy and tourism, as well as the promotion of tourism from a sustainable development perspective. The results obtained lead to the conclusion that the main geostrategic challenges of tourism are related to the need to design policies that seek the conservation of nature, the promotion of sustainability in tourism activities, the local development of communities and the prevention of the environmental hazards of global warming, as well as possible conflict scenarios that negatively influence the development of these activities